School violence: risk factors, prevention and challenges - Valbuena Ancho, Inero; Rei Palces, Krizna (Bullying and victimization, 2019)
"This book attempts to uncover school violence in different contexts by presenting studies of expert practitioners, which highlight concepts, risk factors, prevention mechanisms and challenges faced by concerned individuals in the hope of developing solutions to the occurrence of violence involving school children. Studies included in this book are those of international and national scope, stakeholder involvement, and even the role of new technologies in light of school violence"--